The experiences and needs of hospice care nurses facing burnout: a scoping review - Yu, Jiaxiang; Soh, Kim Lam; He, Liping; Wang, Pengpeng; Soh, Kim Geok; Cao, Yingjuan (SAGE Publications, 2023)
Aim: Explore the existing literature on the experience and needs of palliative nurses facing job burnout. Background: On a global scale, with the increase of aging, the number of people in need of palliative care has increased significantly, which has a huge impact on the professional pressure of palliative nurses. Existing literature focuses on examining palliative care from the perspective of patients, but palliative nurses also face the threats to physical and mental health caused by job burnout. Evaluation: A systematic literature search has been carried out in the following databases as of October 2021:PubMed, EMBASE, CINAHL, Web of Science, and Scopus. The Cochrane Library and Joanna Briggs Institute Library were also searched to confirm if there are any available systematic reviews on the subject. Manually searched the reference list of included papers. Key issues: Seventeen studies were included in this review. Five key issues in the palliative care nurse’s experience: (1) psychological harm, (2) physical symptoms, (3) negative emotions, (4) Burnout caused by communication barriers, and (5) Lack of experience. Two key issues in the needs of palliative care nurses: (1) social support, and (2) training and education. Conclusion: The pressure of facing death for a long time and controlling the symptoms of patients has a very important impact on the mental and physical health of palliative nurses. Nursing staff have needed to be satisfied, and it is essential to provide support and help relieve the pressure on palliative nurses.